ARABIC PROGRAM ON COT KALA LANGSA STREAMING RADIO SEBAGAI STRATEGI BARU PEMBELAJARAN BAHASA ARAB - Dhiauddin, Dhiauddin (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2015)
Learning a language means learn to communicate. The goal of learning Arabic by using communicative approach is to stimulate the student to be able to master both receptive and productive skill. Receptive skills includes listening and reading skill, while productive skills includes speaking and writing skills. The objective of this study is to describe the streaming radio as a strategy in Arabic learning for the student of Arabic Department at Cot Kala Langsa State Islamic Institute. The result at the study shows that the streaming radio strategy gives a good response in conducting the Arabic class. Means that streaming radio can enhance the quality of teaching and learning Arabic at this institute.DOI: 10.15408/a.v2i1.1480